The relationship between race, type of work, and Covid-19 infection rates - R. Jason Faberman; Daniel Hartley (Federal Reserve Bank of Chicago, 2020)
This paper explores the relationship between Covid-19 infection rates, race, and type of work. We focus on three U.S. cities-Chicago, New York, and Philadelphia-allowing us to exploit zip code-level variation in infection rates and testing rates over time, while controlling for a variety of neighborhood demographic characteristics. We find that neighborhoods with higher Black and Hispanic population shares, and neighborhoods with higher shares of workers in high-social contact jobs within essential businesses, had disproportionately higher Covid-19 infection rates, even after applying our testing and demographic controls. These higher rates coincide with citywide peak infection rates, suggesting an amplified response for these groups. Local variation in type of work accounts for relatively little of the variation in infection rates by race. Additional evidence for Arizona, Florida, and Texas also shows amplified infection rates for these groups around statewide peak infection rates, despite their peaks occurring months after the cities in our main sample. Evidence from these states also shows higher infection rates among high-social contact workers in nonessential businesses that coincides with a more aggressive reopening of these businesses.
Keywords: H12; I12; J15; R12; 330; Covid-19 pandemic; infection rates; race; employment; social interaction